Parameter Dependence of Positive Solutions for Second-Order Singular Neumann Boundary Value Problems with Impulsive Effects - Xuemei Zhang (Abstract and Applied Analysis)
The author considers the Neumann boundary value problem -y′′t+Myt=λωtft,yt,  t∈J,    t≠tk,  -Δy′|t=tk = λIktk,ytk,   k=1,2,…,m,  y′(0)=y′(1)=0 and establishes the dependence results of the solution on the parameter λ, which cover equations without impulsive effects and are compared with some recent results by Nieto and O’Regan.